Veterinary epidemiology - Thrusfield, M. V.; Christley, Robert, 1968- (Hoboken, NJ : Wiley Blackwell, 2018)
'A comprehensive introduction to the role of epidemiology in veterinary medicine This fully revised and expanded edition of Veterinary Epidemiology introduces readers to the field of veterinary epidemiology. The new edition also adds new chapters on the design of observational studies, validity in epidemiological studies, systematic reviews, and statistical modelling, to deliver more advanced material. This updated edition begins by offering an historical perspective on the development of veterinary medicine. It then addresses the full scope of epidemiology, with chapters covering causality, disease occurrence, determinants, disease patterns, disease ecology, and much more. Veterinary Epidemiology, Fourth Edition, features updates of all chapters to provide a current resource on the subject of veterinary epidemiology. Presents new chapters essential to the continued advancement of the field. Includes examples from companion animal, livestock, and avian medicine, as well as aquatic animal diseases. Focuses on the principles and concepts of epidemiology, surveillance, and diagnostic-test validation and performance. Includes access to a companion website providing multiple choice questions Veterinary Epidemiology is an invaluable reference for veterinary general practitioners, government veterinarians, agricultural economists, and members of other disciplines interested in animal disease. It is also essential reading for epidemiology students at both the undergraduate and postgraduate levels'--Provided by publisher.
The development of veterinary medicine -- The scope of epidemiology -- Causality -- Describing disease occurrence -- Determinants of disease -- The transmission and maintenance of infection -- The ecology of disease -- Patterns of disease -- Comparative epidemiology -- The nature of data -- Data collection and management -- Presenting numerical data -- Surveys -- Demonstrating association -- Observational studies -- Design considerations for observational studies -- Clinical trials -- Validity in epidemiological studies -- Systematic reviews -- Diagnostic testing -- Surveillance -- Statistical modelling -- Mathematical modelling -- Risk analysis -- Economics and veterinary epidemiology -- Health schemes -- The control and eradication of disease -- General reading -- Appendices -- Appendices. Glossary of terms -- Basic mathematical notation and terms -- Some computer software -- Veterinary epidemiology on the Internet -- Student's t-distribution -- Multipliers used in the construction of confidence intervals based on the Normal distribution, for selected levels of confidence -- Values of exact 95% confidence limits for proportions -- Values from the Poisson distribution for calculating 90%, 95% and 99% confidence intervals for observed numbers from 0 to 100 -- The [chi]2 distribution -- Technique for selecting a simple random sample -- Sample sizes -- The probability of detecting a small number of cases in a population -- The probability of failure to detect cases in a population -- Sample sizes required for detecting disease with probability, p1, and threshold number of positives -- Probabilities associated with the upper tail of the Normal distribution -- Lower- and upper-tail probabilities for Wx, the Wilcoxon-Mann-Whitney rank-sum statistic -- Critical values of T+ for the Wilcoxon signed ranks test -- Values of K for calculating 95% confidence intervals for the difference between population medians for two independent samples -- Values of K* for calculating 95% confidence intervals for the difference between population medians for two related samples -- Common logarithms (log10) of factorials of the integers 1-999 -- The correlation coefficient -- The variance-ratio (F) distribution.
Includes bibliographical references and index.
Description based on online resource; title from electronic title page (Wiley Online Library, viewed July 31, 2018).
Keywords: Veterinary epidemiology; Epidemiologic Methods -- veterinary